Exploring Approaches to Integrating Global Competency Education in Chinese High School English Classrooms-Based on the background of PISA Analysis - Zhenghong Shen; Wang Yue (Journal on Education, 2023)
Based on the background of PISA analysis, the paper aims to explore suitable approaches to integrating global competency education into Chinese high school English classroom. The paper first introduces several important concepts including global competency、 PISA (Program for International Student Assessment) and its background analysis, then takes Chinese high school English classrooms as the entry point to explore the necessity and feasibility of integrating global competency education with Chinese high school English, and finally summarizes the realistic approaches of integration combined with the international implementation of global competency education. The approaches are that 1) English teaching should focus on global issues and conduct thematic exploration. 2) English teaching should carry out“invitation style” subject integration. 3) English teaching should enrich teaching strategies and adopt multi-perspective teaching method.